Analisis Fraud Diamond dalam Mendeteksi Financial Statement Fraud - Nadianti, Nurul; Bagianto, Agus; Hanim, Wasifah (Universitas Muhammadiyah Metro, 2025)
FFinancial statement fraud and early detection of fraudulent activities are very important before they become major cases that can harm the company. This study was conducted to see how much influence fraud diamonds have on financial statement fraud. The independent variables in this study consist of pressure, opportunity, rationalization, and capability. While the dependent variable in this study is financial statement fraud proxied by the Beneish m-score. The object of the study is Transportation & Logistic companies in Indonesia in 2019-2023 and listed on the IDX, using purposive sampling techniques obtained 37 companies. The data analysis method used is logistic regression analysis. The results of the study stated that pressure and opportunity did not affect financial statement fraud, while rationalization and capability had a positive effect on financial statement fraud